Neotectonics as a structural control of the boundaries of the Pantanal Matogrossense Sub-Regions - MIOTO,CAMILA L. (2019)
Abstract: Characterized by fluvio-alluvial sedimentation processes, the heterogeneity in the Pantanal Basin allows its division in several sub-regions, which present natural characteristics of their own. It is possible to find in the literature different proposals to subdivide the Pantanal plain, which vary in total area and number of sub-regions. Each author uses specific criteria – mainly vegetation, soil and humidity – in his delimitation, but does not consider the tectonic aspects of the basin. In this sense, we intend to analyze three Pantanal delimitations from the literature and to relate them to the neotectonic context of the Pantanal plain by comparing the boundaries proposed in the delimitations to structural lineaments present in the basin. As a result, we observe that the comparison of the Pantanal boundaries with the lineaments shows a high compatibility between them, suggesting the influence of these structures in the development of the sub-regions.